The use of IT tools in the accident investigation and analysis process based on the example of foundries - Racek, Elżbieta; Gruszka, Józef (Wykorzystanie narzędzi informatycznych w procesie badania i analizy wypadkowości na przykładzie odlewni, 2019)
Accidents at work sooner or later affect every enterprise. It is the employer’s responsibility to ensure safe working conditions by determining occupational risk at all workplaces, combating sources of danger, and providing employees with relevant information and instructions. This is one of the effective ways to reduce the number of accidents at work. The purpose of the article is to analyze accidents at work in the period 2014-2018 in a selected foundry enterprise in Wielkopolska. The scope of the article includes a summary of the data from the Central Statistical Office, the characteristics of the enterprise, and the hazards occurring in the foundry process. An analysis and assessment of accident rates at the foundry in the same period were also presented. The assessment was based on accident rates, on the basis of which the work station most vulnerable to accidents was determined
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 3 (53), s. 62-73
Keywords: accidents at work; industrial foundry; safety; hazards; wypadki przy pracy; odlewnia przemysłowa; bezpieczeństwo; zagrożenia